Implementation Of Public Services In The Digital Era As A Public Information Media Regional Government Of Jayapura Regency, Papua Province - Muhammad Sawir; Salahudin Robo; Faisal Abubakar; Santrio Kamaluddin (Universitas Padjadjaran, 2023)
Technology is present in human life with the intention of facilitating all kinds of activities that can be accessed by the community. As a result, technology is considered to have a fairly high efficiency value. Along with the development of the technological era, the government has managed to take advantage of this to carry out activities related to public services that have a clear legal basis for implementation, but there are still people in Jayapura Regency who do not know about the website, due to different constraints in each sub-district. The purpose of this study is to find out whether the Jayapura Regency Regional Government Website has been operating properly, as well as to identify the challenges faced and possible solutions. Alvaro Roscha's theory is used in this qualitative descriptive research method on the Jayapura Regency Government website. The method used to collect data includes observation and interviews. Research Results The Jayapura Regency Regional Government website is considered to function well, although the complaint system is still problematic and has not been able to provide a satisfactory response to the public. In addition, the Jayapura Regency Communication and Informatics Office has succeeded in effectively managing the Jayapura Regency Government website, although it still encounters obstacles such as pages that cannot be accessed, complaints that have not been handled, and the appearance of the website which is still simple to improve quality. Jayapura Regency Government, in this case the Ministry of Communication and Informatics can provide website technology training.